2017
DOI: 10.1177/0020764017704474
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of socially withdrawn youth in France: A retrospective study

Abstract: Over one-third of Psymobile patients aged 18-34 years were referred on grounds of social withdrawal. Our data may illustrate more accurately the situation of youth social withdrawal amid the general population than data from help-seeking patients or online questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 21 publications
3
47
3
4
Order By: Relevance
“…Hikikomori or similar phenomena have been reported in various other countries, including France [9], Australia, Thailand, Taiwan, Bangladesh, Iran, India, Korea, the USA [10,11], Oman [12], and Spain [13]. An epidemiological study of hikikomori in Japan in a community-based population aged 20-49 years revealed that 1.2% of that population had experienced the phenomenon in their lifetime [14], while a cross-sectional telephone-based survey in Hong Kong revealed that 1.9% of 12-29-year-olds had experienced it [15].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Hikikomori or similar phenomena have been reported in various other countries, including France [9], Australia, Thailand, Taiwan, Bangladesh, Iran, India, Korea, the USA [10,11], Oman [12], and Spain [13]. An epidemiological study of hikikomori in Japan in a community-based population aged 20-49 years revealed that 1.2% of that population had experienced the phenomenon in their lifetime [14], while a cross-sectional telephone-based survey in Hong Kong revealed that 1.9% of 12-29-year-olds had experienced it [15].…”
Section: Introductionsupporting
confidence: 79%
“…In the current study, many individuals with hikikomori were long-term cases, compared with previous research targeting 18-to 34-year-olds in France (mean duration = 29 months; [9]) and 16-to 35-year-olds in Japan (mean duration = 4.3 years; [5]). However, recent epidemiological studies in Japan have shown that 34.7% of individuals with hikikomori aged between 15 and 39 years have had the disease for more than 7 years [25,37], while 38.2% of those aged between 40 and 64 years have had hikikomori for more than 7 years [26].…”
Section: Discussioncontrasting
confidence: 49%
“…In 2010, we conducted the first international hikikomori survey targeting psychiatrists in Australia, Bangladesh, Iran, India, Japan, South Korea, Taiwan, Thailand, and the USA using two case vignettes in a self‐reporting format and showed the possibility of a hikikomori ‐like phenomenon in all the countries surveyed . Thereafter, the cases of hikikomori sufferers in countries including France, Spain, Italy and Brazil were reported . Epidemiological surveys of hikikomori outside Japan are very limited.…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 99%
“…9,18 Thereafter, the cases of hikikomori sufferers in countries including France, Spain, Italy and Brazil were reported. [38][39][40][41][42][43][44] Epidemiological surveys of hikikomori outside Japan are very limited. In Hong Kong, a telephone-based epidemiological survey has revealed that hikikomori sufferers (duration 6 months and over) account for 1.9% of the population.…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 99%
“…O tempo médio de confinamento foi de 17 meses, 39% tinham história familiar de doença psiquiátrica e 43,9% sofreram abuso ou negligência na infância. Os jovens reclusos tinham relacionamento hostil com os familiares, especialmente com os pais.Na França, Chauliac et al15 estudaram 66 indivíduos com isolamento social prolongado entre 18 e 34 anos de idade e verificaram que 80% eram do sexo masculino, 42% nunca haviam tido contato com um profissional de saúde mental, 42% faziam uso de cannabis, 71% mantinham contato com seus familiares, 42% eram hostis verbalmente e 73% saiam de casa esporadicamente. O tempo médio de reclusão foi de 29 meses e metade deles havia recebido o diagnóstico de um transtorno psiquiátrico antes da pesquisa.…”
unclassified